Decentralising scientific publishing: can the blockchain improve science communication? - Coelho, Flávio Codeço; Brandão, Adeilton (Memórias do Instituto Oswaldo Cruz, 2019)
We present a decentralised solution for managing scientific communication, based on distributed ledger technologies, also called blockchains. The proposed system aims to solve incentive problems displayed by traditional systems in scientific communication and publication. A minimal working model is presented, defining roles, processes, and expected results from the novel system. The proposed solution is viable, given the current status of blockchain technology, and should lead to a rethinking of current practices and their consequences for scientific communication.